TANGGUNG JAWAB ANGGOTA MAJELIS TAKLIM DALAM MELAKSANAKAN KEGIATAN SOSIAL DI PERUMAHAN ARENGKA INDAH KOTA PEKANBARU - Refina Sari Sari; Daeng Ayub Natuna Ayub Natuna; Desti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Formulation of the problem in this study is how much the responsibility of Majelis Taklim Members in social activity at Arengka Indah Housing in Pekanbaru City. The purpose of this study is determine the level of the responsibility of Majelis Taklim Members in social activity at Arengka Indah Housing in Pekanbaru City. The benefits of this research can add insight into the responsibility of Majelis Taklim Members in social activity at Arengka Indah Housing in Pekanbaru City. This is a descriptive syudy with a quantitative approach. The populations are 60 people. The sample in this study used random sampling. The instrument used in this study was a questionnaire containing 54 items statement, the responsibility of Majelis Taklim Members in social activity at Arengka Indah Housing in Pekanbaru City with indicators: (1) the responsibility to self; (2) the responsibility to family; (3) the responsibility to society; (4) the responsibility to Nation and Country; (5) the responsibility to God. From the research result showa that the responsibility of Majelis Taklim Members in social activity at Arengka Indah Housing in Pekanbaru City referred to this study is the responsibility of Majelis Taklim members in high category. Key word: The Responsibility, Majelis Taklim members, Social Activity